Efecto del cambio del paisaje en la estructura de la comunidad de abejas sin aguijón (Hymenoptera: Apidae) en Meta, Colombia - Nates Parra, Guiomar (2008)
Stingless bees represent one of the most diversified components of the natural Apoidea fauna of pollinators in the tropics. They use diverse kinds of substrates and inhabit varied habitats. Some species are typical for some natural either artificial place. The landscape alteration were this group of bees nests, has and important impact on the natural composition of its community structure, fact which is reflected in the nest density. We analyzed the structure composition of the stingless bees’ community in three environments in the Colombian llanos piedmont, an important region that represents the transition between Andean ecosystems and a savannah that is seriously threatened by cattle practices. We made systematic samples in secondary forest, agro-ecosystems and urban areas, recording the presence of 204 nests from 11 genera (24 species). The nest density per landscape was heterogeneous and never higher than 16 nests/Ha. We observed two nesting patterns and an effect of sampling criterion on the measured biodiversity.